Цінність архівних матеріалів для сучасних наукових досліджень діяльності дореволюційних університетів України щодо становлення та розвитку системи приват-доцентури - Таможська, Ірина (Видавництво Львівської політехніки, 2017)
An array of historical and pedagogical sources that allowed us to reproduce the process of introducing the Privat Assistant Professorship Institute in the Novorossiysk (Odesa), the Kharkiv and St. Vladimir (Kyiv) Universities, and illuminate the objective and subjective reasons, that hinder significant growth of number of privat-docents is analyzed in the article. We studied and used in our work archival works that include information about the appointment of candidates as privat-docents, evaluation of their scientific experience, the quality demo and introductory lectures.
Keywords: pre-revolutionary time; privat assistant professorship; pro venia legendi; scientific and pedagogical staff; dissertation